EVALUATION OF CALCIUM CARBONATE CONTENT IN EGGSHELLS OF AVIAN, TURTLE, SNAIL, AND OSTRICH USING CHEMICAL ANALYSIS AND SCANNING ELECTRON MICROSCOPY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
In the present study, different eggs were collected and analyzed from five various animal species: European pond turtle (Emys orbicularis (Linnaeus, 1758)), giant African land snail (Achatina fulica (Bowdich, 1822)), common ostrich (Struthio camelus (Linnaeus, 1758)), white, light-brown, and dark-brown laying hen (Gallus gallus domesticus (Linnaeus, 1758) and European quail (Coturnix coturnix (Linnaeus, 1758). The typical mineral shell mainly composed of the calcite polymorph of CaCO3 but the eggshell consists of membranes, that composed mainly of proteins. The shell quality also could be assigned by several external and internal factors such as oviposition time, animal genotype and age, housing system (for poultry), and mineral nutrition complex. The CaCO3 content was determined by the standard titration method, coz the titration could provide a reliable method for evaluation of CaCO3 content in different types of eggshells. The structural surface characterization of eggshells was performed by scanning electron microscopy (SEM) with a field emission gun. In terms of chemical composition, ostrich eggshells generally did not differ much from those of laying hen, turtles, giant snails, or quail eggs, but the concentration of calcium carbonate was the highest. The average calcium carbonate content of various eggshells is between 84 and 98%. The thickness of the eggshell ranges from 0.08 to 1.89 mm, and it  is not the same over the entire surface of the egg. At the sharp end of the egg, the shell is slightly thicker than at the blunt end. The purpose of this study was to study the quantitative content of calcium carbonate in various eggshells of different animals to draw further conclusions in which animals the eggshell contains the maximum amount of biological calcium carbonate.